The efficacy of traditional Thai massage in decreasing spasticity in elderly stroke patients - Thanakiatpinyo, Thanitta (Dove Medical Press, 2014)
PURPOSE: To study the efficacy of traditional Thai massage (TTM) versus conventional physical therapy (PT) programs in treating muscle spasticity, functional ability, anxiety, depression, and quality of life (QoL) in Thai stroke patients. METHODS: This randomized controlled trial with a blinded assessor was carried out at the Department of Rehabilitation Medicine, Siriraj Hospital (Bangkok, Thailand). The study included 50 stroke (onset ≥3 months) outpatients experiencing spasticity at the elbow or knee muscles at a grade of ≥1+ on the modified Ashworth Scale who were ≥50 years old and able to communicate. The subjects were randomly allocated to the treatment group receiving TTM (24 subjects) or the control group receiving the PT program (26 subjects). Both groups received treatment (either TTM or PT) twice a week for 6 weeks. Spasticity grade, functional ability, anxiety, depression, and QoL were measured at Week 0 and Week 6. RESULTS: At Week 6, the percentage of patients whose modified Ashworth Scale score had decreased by at least one grade was not statistically significant between the two groups. Both TTM and PT groups experienced a significant increase in functional ability and QoL, but no difference was found between the groups. Anxiety and depression scores showed a decreasing trend in the TTM group. CONCLUSION: This preliminary report showed no evidence that TTM differed from the PT program in decreasing spasticity. However, both interventions may relieve spasticity, increase functional ability, and improve QoL after 6 weeks. Only TTM can decrease anxiety and depression scores. Further studies with adequate sample size are necessary.